Looking out, looking in : anthology of Latino poetry - Luis, William (Arte Público Press, 2013)
A comprehensive anthology that focuses on poetry from the four largest Latino groups in the United States: Mexican Americans, Cuban Americans, Puerto Ricans and Dominican Americans. Includes works from more than 80 Latino poets writing from the mid-twientieth century to the present, dealing with a variety of issues from those specific to the Hispanic experience to more universal concerns.